Thermal stability of lead-free CH3NH3SnxI3 systems (0.9 ≤ x ≤ 1.1) for photovoltaics. (September 2017) - Dimesso, L.; Fasel, C.; Lakus-Wollny, K.; Mayer, T.; Jaegermann, W.
Abstract: Methylammonium-tin-iodide (MASn x I3, 0.9 ≤ x ≤ 1.1) systems were prepared by precipitation process in aqueous solutions. The "as prepared" MASn x I3 systems exhibited a tetragonal crystalline phase (space group I 4 cm ) with polyhedral crystallites (length 50–400 µm). The as prepared samples were annealed at T = 150 °C for t = 8 h under nitrogen and synthetic air. Under nitrogen, the CH3 NH3 Sn x I3 systems adopt nearly-cubic tetragonal structure (space group P 4 mm ) with crystallites of 2–4 µm length whereas a degradation process with formation of non-crystalline phases occurred in air. The differential thermal analysis (DTA) profile in nitrogen revealed events at T = 247 °C, T = 297 °C (decomposition of CH3 NH3 Sn x I3 systems into methylamine (CH3 NH2 ), hydroiodic acid (HI) and SnI2 ), and in the range T = 342–373 °C (melting of SnI2 ) respectively. The thermal profile in air showed endothermic events at T = 139 °C and T = 259 °C with additional events at onset temperatures of T = 337 °C and T = 423 °C respectively which correspond to the formation of Sn(IV)-O binds and to the decomposition of methylamine. Static thermogravimetry analysis (TG), performed at T = 85 °C and T = 150 °C for t = 2 h, revealed a linear weight loss as a function of the time. The optical absorption spectra displayed absorbance edges in near infrared range, at 1107.0 nm ( x = 0.9), 1098.6 nm ( x = 1.0) and 1073.2 nm ( x = 1.1) respectively.